Rankeles' interethnic policies during the second half of the 19th century (Quinto Sol, 2013)
In the context of studies concerning the Southern Frontier, this paper wants to characterise the policy that ranqueles developed towards the emerging Argentinian State during the second half of the 19th century. Specifically, it attempts to identify and explain the changes and continuities in the political actions from the main ranqueles chief according to the different drawbacks that affected the creation of the Argentinian State. In this sense, the work states that during the 1870´s the relationship between indigenous and cristianos had turned into assimetrical one, due to the fact that the National Government from that period had succeeded in turning into the unique interlocutor with which the ranqueles could act. To support this statement, the text describes the alliances and counteralliances that appeared in the period 1850-1880 between the ranqueles and the different cristianos sectors, since they demonstrate that as the Argentinian State was imposing over the opposition groups to its formation, the indigenous faced deterioration of their capacity of political action. In this way, it examines first the events from the 50´s as they give account of the great role that the indigenous played when the Argentine Confederation and the Province of Buenos Aires were confronting. Later, it analyses the events from the 60´s when the ranqueles joined their forces to the federal groups in opposition to the leadership of Buenos Aires. Finally, it studies the indigenous actions prior to their subjugation.
Keywords: Ranqueles; Argentinian State; indigenous policy; peace treaty; alliances